Implementasi Pengaturan Pajak Karbon dalam Rangka Mewujudkan Pembangunan Berkelanjutan di Indonesia - Rudi Hartono; Didik Suhariyanto; Ismail (Jurnal Hukum Lex Generalis, 2025)
Climate change is a pressing global challenge, with Indonesia, the world's sixth-largest carbon emitter, facing pressure to reduce greenhouse gas emissions. This study analyzes Indonesia's carbon tax regulations as an environmental fiscal instrument in support of equitable sustainable development. The research objective is to analyze carbon tax regulations in support of equitable sustainable development and to assess the effectiveness of carbon tax regulations as an instrument for achieving sustainable development in Indonesia. This study uses a normative juridical method with legislative, conceptual, comparative, and limited empirical approaches. Primary legal materials include Law Number 7 of 2021 concerning the Harmonization of Tax Regulations and Presidential Regulation Number 98 of 2021 concerning the Implementation of Carbon Economic Value. The research findings indicate that the carbon tax system has adopted the polluter pays principle and social justice, but still faces structural weaknesses in the form of unclear formulation, low tariffs (Rp30,000/kg CO₂e), limited sector coverage (35% of national emissions), and the absence of adequate social compensation mechanisms. The effectiveness of carbon tax implementation is hampered by limited implementing regulations, an immature MRV system infrastructure, weak cross-sectoral coordination, and potential regressive impacts on low-income groups. This research recommends the development of a comprehensive carbon tax roadmap, strengthening the MRV system, establishing a fair social compensation mechanism, transparency in tax revenue allocation, and harmonization of cross-sectoral policies to ensure that the carbon tax can function effectively as an instrument of equitable sustainable development in Indonesia.